THE IMPACT OF REAL-TIME LIVE STREAMING INTERACTIVITY ON CONSUMER ENGAGEMENT AND IMPULSIVE BUYING - Septya Nurul Magisa; Nindy Puspitasari; Nur Hidayat (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
The expansion of live streaming commerce has transformed customer shopping behaviors by amalgamating entertainment, engagement, and immediate purchasing into a cohesive experience. This research examines the impact of real-time live streaming interactivity on consumer engagement and impulsive purchasing via the lens of the Stimulus-Organism-Response theory. Data were gathered via a survey of Generation Z consumers engaged in live streaming shopping and analyzed using WarpPLS with structural equation modeling. The results indicate that interactivity markedly improves consumer involvement, hence reinforcing impulsive purchasing behavior. Furthermore, interaction directly impacts impulsive purchasing, affirming that prompt communication and interactive elements enhance both engagement and spontaneous buying decisions. Engagement serves as a vital intermediary, converting interactive stimuli into consumer reactions. This study enhances the theoretical application of the S-O-R model in digital commerce and offers practical advice for e-commerce platforms and streamers to develop balanced interactive methods that optimize engagement while reducing post-purchase unhappiness.